Periodontitis contributes to COPD progression via affecting ferroptosis - Kaixin Xiong; Peng Yang; Wei Wei; Jia Li; Yujia Cui; Yan Li; Boyu Tang (BMC, 2023)
Abstract Background Periodontitis has emerged as a potential risk factor for chronic obstructive pulmonary disease (COPD). However, the precise mechanism through which periodontitis influences the progression of COPD requires further investigation. Ferroptosis is one of the crucial pathogenesis of COPD and recent researches suggested that periodontitis was associated with ferroptosis. Nonetheless, the relationship among periodontitis, COPD and ferroptosis remains unclear. This study aimed to elucidate whether periodontitis contributes to COPD exacerbation and to assess the potential impact of ferroptosis on periodontitis affecting COPD. Methods The severity of COPD was assessed using Hematoxylin and eosin (H&E) staining and lung function tests. Iron assays, malondialdehyde (MDA) measurement and RT-qPCR were used to investigate the potential involvement of ferroptosis in the impact of periodontitis on COPD. Co-cultures of periodontitis associated pathogen Phophyromonas gingivalis (P. gingivalis) and lung tissue cells were used to evaluate the effect of P. gingivalis on inducing the ferroptosis of lung tissue via RT-qPCR analysis. Clinical Bronchoalveolar Lavage Fluid (BALF) samples from COPD patients were collected to further validate the role of ferroptosis in periodontal pathogen-associated COPD. Results Periodontitis aggravated the COPD progression and the promotion was prolonged over time. For the first time, we demonstrated that periodontitis promoted the ferroptosis-associated iron accumulation, MDA contents and gene expressions in the COPD lung with a time-dependent manner. Moreover, periodontitis-associated pathogen P. gingivalis could promote the ferroptosis-associated gene expression in single lung tissue cell suspensions. Clinical BALF sample detection further indicated that ferroptosis played essential roles in the periodontal pathogen-associated COPD. Conclusion Periodontitis could contribute to the exacerbation of COPD through up-regulating the ferroptosis in the lung tissue.